Income Inequality as Long-term Conditioning Factor of Monetary Transmission to Bank Interest Rates in EA Countries - Tomas Domonkos; Boris Fisera; Maria Siranova (Charles University in Prague, Institute of Economic Studies (IES), 2021)
In this paper we investigate the effect of income inequality on the transmission of standard and unconventional monetary policy shocks to bank loan rates. We hypothesize that income inequality might encapsulate important characteristics of credit market demand. We use an interacted panel error correction model to examine a set of EA countries over the years 2008-2016. Our findings suggest that higher income inequality hinders the transmission of standard monetary policy to consumer loans and limits the use of unconventional monetary policy in the housing loans segment. Conversely, more unequal societies are characterized by stronger monetary transmission in the small firm loans segment.
Keywords: D31; E21; E52; E58; 330; interest-rate pass-through; interacted PMG; income inequality; standard monetary policy; unconventional monetary policy